Hepatoprotective Effect of Citrus sinensis (L.) Osbeck Ethanol Extract in Paracetamol-Induced Rats (Majalah Kedokteran Bandung, 2019)
Based on data from the National Poison Data System of the American Association of Poison Control Center, it is reported that there is a high number of death and liver transplantation due to paracetamol and other combination drugs of paracetamol toxicity. Citrus sinensis (L.) Osbeck (Sunkist) is a fruit that has been widely studied for its various therapeutic effects. This study aimed to explore the potential of Sunkist peels as a hepatoprotection agent against the toxicity of paracetamol. This was an experimental study conducted in May 2019 at the Pharmacy Biology Laboratory of Pharmacy Faculty, University of North Sumatera on 15 rats that were divided into 5 groups of treatment (negative, positive, and 300, 450, and 600 mg/kgBW Sunkist ethanol extract) and received treatment for 14 days. The AST and ALT was assessed using the dyasis manual assay. Data were then analyzed using one-way ANOVA, followed by Post-hoc test. The results of this study showed that the ALT and AST levels were significantly different (P-value
Keywords: ALT; AST; Citrus sinensis L. Osbeck; ethanol; paracetamol; sunkist